Physical determinants of golf swing performance: a review - Sheehan, W. B.; Bower, R. G.; Watsford, M. L. (The Journal of Strength and Conditioning Research, 2022)
Traditionally, golf practice has primarily focused on the mental, technical, and skill aspects as the primary means to improve performance. Only recently has a greater emphasis been placed on the physical components with balance, muscular strength, power, and specific muscle-tendon properties demonstrating positive associations with club head speed and carry distance. Accordingly, this review will explore the influence of these physical components on measures of golf swing performance. Superior balance may allow players to effectively deal with the need to shift weight during the swing as well as different stance positions, whereas superior lower-body muscular strength, power, and stiffness may allow more mechanical work to be performed on the club during the swing per unit of time, consequently increasing club head speed. Alternatively, flexibility may also contribute to enhanced force production with a greater range of motion, particularly when generating the "X-factor," allowing for a longer backswing and more time to produce higher angular velocities and forces. Furthermore, training intervention studies focusing on the aforementioned components have demonstrated enhancements in swing performance. Targeting multiple muscle groups, including those implicated via electromyography activation, and utilizing multiple modalities have proven effective at increasing club head speed. However, such multifaceted programs have made it difficult to determine the mechanisms that specifically contribute to performance gains. Despite these limitations, strength, power, and musculotendinous stiffness, particularly in the lower body, seem to be stronger determinants of club head speed and carry distance than flexibility. Furthermore, acute improvements can be induced using resistance-orientated warm-ups.